Syûrâ Dan Demokrasi Dalam Kajian Fiqh Siyâsah - Yusuf Faisal Ali (STAI Siliwangi Bandung, 2017)
In studies of siyâsah fiqh, shura (consultation) is an obligatory constitutional principle to be implemented in an Islamic government as a means to reach consensus in politics and to control executive power. Such roles prevent dictatorship and unfair acts of a ruler. Nevertheless, in its conceptual and praxis levels, shura crosses path with modern democracy, a western product. This meeting point gives birth to discourses and speculations that are diversely appreciated by Islamic scholars represented by this question: are the two notions identical? This issue requires analysis by elaborating boundaries of similarities and differences in the principles of the two concepts in order to obtain a holistic and proportional account. Analysis reveals that shura and democracy are distinctive concepts. Such a conclusion is drawn due to differences in terms of both principles and implementation. On the other hand, both concepts are not conflicting since democracy can be part of Islamic political system as long as it is oriented towards and its system of values are based upon religious and morality values.